A comparison of laser with radiofrequency ablation for the treatment of benign thyroid nodules: a propensity score matching analysis. (17th November 2017) - Pacella, Claudio Maurizio; Mauri, Giovanni; Cesareo, Roberto; Paqualini, Valerio; Cianni, Roberto; De Feo, Pierpaolo; Gambelunghe, Giovanni; Raggiunti, Bruno; Tina, Doris; Deandrea, Maurilio; Limone, Pier Paolo; Mormile, Alberto; et al.
Abstract: Purpose: To compare technique efficacy and safety of laser ablation (LA) and radiofrequency ablation (RFA) in treatment of benign thyroid nodules. Materials and methods: Institutional review board approval was obtained, and patients' consent was waived. 601 nodules were treated from May 2009 to December 2014 at eight centres, 449 (309 females, age 57 ± 14 years) with LA and 152 (107 females, age 57 ± 14 years) with RFA. A matched cohort composed of 138 patients from each group was selected after adjustment with propensity score matching. Factors influencing volume reduction at 6 and 12 months and complications were evaluated. Results: No significant differences were observed in the baseline characteristics between groups after propensity score matching adjustment. Mean nodule reduction at 6 and 12 months was −67 ± 19% vs. −57 ± 21% ( p  < 0.001) − 70 ± 19% vs. −62 ± 22% ( p = 0.001) in LA group and in RFA group, respectively. Nodules with volume >30 mL had significantly higher percentage volume reduction at 6 and 12 months (−69 ± 19 vs. −50 ± 21, p  = 0.001) and (−73 ± 18 vs. −54 ± 23 8, p  = 0.001) in the LA group than in the RFA group, respectively. In both groups, operator's skills affected the results. Major complications occurred in 4 cases in each group ( p  = 0.116) Conclusions: LA and RFA showed nearly similar outcome but LA was slightly more effective than RFA in large nodules. Operator's skills could be crucial in determining the extent of nodule volume reduction regardless of the used technique.